Strategi Pembelajaran Ekstrakurikuler Karawitan Di SMA Negeri 1 Pemalang - Iswangga, Komara Dika; Muttaqin, Moh Muttaqin; Wiyoso, Joko (Universitas Negeri Semarang, 2020)
The Learning strategies are learning components that must be applied in learning activities by teacher, including learning of karawitan extracurricular in High School 01 Pemalang. The purpose of this study is to describe the learning strategies used by teachers in karawitan extracurricular of High School 01 Pemalang, uses descriptive qualitative study methods. The data collection is obtained through observation, interviews, and documentation technique. While validity of the data was tested using source triangulation techniques, then data analysed by interactive analysis technique. The results showed that the learning strategies in karawitan extracurricular of High School 01 Pemalang was using a teacher-centered, that the teacher becomes the center of the learning which determines the material, methods, dan learning objectives. Then, the syntax (stage) of learning strategies are orientation, presentation, guided training, structured training, independent training, independet activities, and evalution.